2010
DOI: 10.1038/ejcn.2010.114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy obesity: different prevalences using different criteria

Abstract: Objective: To estimate the prevalence of metabolically healthy obesity (MHO) according to different definitions. Methods: Population-based sample of 2803 women and 2557 men participated in the study. Metabolic abnormalities were defined using six sets of criteria, which included different combinations of the following: waist; blood pressure; total, high-density lipoprotein or low-density lipoprotein-cholesterol; triglycerides; fasting glucose; homeostasis model assessment; high-sensitivity C-reactive protein; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
186
4
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(221 citation statements)
references
References 36 publications
21
186
4
10
Order By: Relevance
“…The lack of consensus criteria to define MHO does not allow the accurate estimation of the prevalence of the MHO and MAO phenotypes, making the comparison between different studies difficult (4,7). In this sense, the reported prevalence of MHO varies widely, ranging from 3 to 57% of obese patients, depending on the method used to define this condition (5,(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of consensus criteria to define MHO does not allow the accurate estimation of the prevalence of the MHO and MAO phenotypes, making the comparison between different studies difficult (4,7). In this sense, the reported prevalence of MHO varies widely, ranging from 3 to 57% of obese patients, depending on the method used to define this condition (5,(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we have previously demonstrated that only 5% of all obese subjects were considered as MHO by all six definitions used (Velho et al, 2010). As no consensus exists regarding the definition of MHO, it is thus understandable that the conclusions of the statistical analyses are also not unequivocal.…”
Section: Discussionmentioning
confidence: 96%
“…Determination of the prevalence of metabolically healthy obese individuals The diagnosis of MHO was obtained based on a BMIX30 kg/m 2 and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;AguilarSalinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009), as described in a previous paper (Velho et al, 2010). As one definition of MHO includes CRP levels (Wildman et al, 2008), analysis of CRP levels was not performed for this definition.…”
Section: Biological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pima Indians, who have the highest prevalence of reported obesity in the world, have a low prevalence of hypertension [47]. To summarise, the genetic pleiotropic associations may in part explain why some obese individuals remain metabolically healthy despite having excessive accumulation of body fat [48][49][50][51][52][53]. This phenomenon is described in the current literature as 'healthy obesity' and, to date, little is known about the factors that protect obese individuals from metabolic disturbances [54].…”
Section: Discussionmentioning
confidence: 99%